Case-control studies on the relationship between onchocerciasis and epilepsy: systematic review and meta-analysis. - Christoph Kaiser; Sébastien D S Pion; Michel Boussinesq (Public Library of Science (PLoS), 2013)
OBJECTIVE: A systematic review and meta-analysis of all available case-control studies on the relationship between onchocerciasis and epilepsy. Because age and level of onchocerciasis endemicity in the area of residence are major determinants for infection, an additional analysis was performed, restricted to studies achieving control of these confounding factors. DATA SOURCES: Medical databases, the "African Neurology Database, Institute of Neuroepidemiology and Tropical Neurology, Limoges," reference lists of relevant articles, commercial search engines, up to May 2012. METHODS: We searched for studies examining infection status with Onchocerca volvulus in persons with epilepsy (PWE) and without epilepsy (PWOE) providing data suitable for the calculation of pooled odds ratios (ORp) and/or standardized mean differences (SMD) using random-effects models. RESULTS: Eleven studies providing data of qualitative skin biopsies for diagnosis of onchocerciasis were identified. Combined analysis on the total sample of 876 PWE and 4712 PWOE resulted in an ORp of 2.49 (95% confidence interval (95%CI): 1.61-3.86, p<0.001). When this analysis was restricted to those studies achieving control for age, residence and sex (367 PWE, 624 PWOE), an ORp of 1.29 (95% CI: 0.93-1.79; p = 0.139) was found. Presence of nodules for diagnosis of onchocerciasis was analyzed in four studies (225 PWE, 189 PWOE; ORp 1.74; 95%CI: 0.94-3.20; p<0.076), including two studies of the restricted analysis (106 PWE, 106 PWOE; ORp 2.81; 95%CI: 1.57-5.00; p<0.001). One study examined quantitative microfilariae counts in patients without preceding microfilaricidal treatment and demonstrated significantly higher counts in PWE than in PWOE. INTERPRETATION: Our results strengthen the hypothesis that, in onchocerciasis foci, epilepsy and infection with O. volvulus are associated. Analysis of indicators giving information on infection intensity, namely nodule palpation and quantitative microfilaria count in untreated patients, support the hypothesis that intensity of infection with O. volvulus is involved in the etiology of epilepsy.